Understanding rice price formation in Central Java: Interactions between market forces, food security, and climate anomalies - Rachman, M Aulia (Journal of Economics Research and Policy Studies, 2025)
This study analyzes the complex factors influencing rice prices in Central Java, Indonesia, during 2018-2024 using panel data analysis. The findings reveal that while cooking oil and sugar prices generally exhibit a positive influence on rice prices via consumption spillovers, the effect of cooking oil became negative in 2021-2024. Domestic rice production significantly depresses prices, whereas food consumption expenditure shows a positive correlation. The Regional Food Security Index (FSI) negatively correlates with rice prices, and the disparity related to the government's Maximum/Highest Retail Price (HET) ratio is positively correlated. Notably, El Niño 3.4 index anomalies consistently drive rice prices upward, highlighting climate vulnerability. Policy implications emphasize integrated interventions encompassing inflation control, production stabilization, food security enhancement, HET evaluation, and climate change mitigation. Additionally, it recommends stronger institutional coordination in rice price and supply chain management.